2023
DOI: 10.3390/antiox12030656
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone B Induces ROS-Dependent Apoptosis in Oxaliplatin-Resistant Colorectal Cancer Cells via p38/JNK MAPK Signaling

Abstract: Licochalcone B (LCB) exhibits anticancer activity in oral cancer, lung cancer, and hepatocellular carcinoma cells. However, little is known about its antitumor mechanisms in human oxaliplatin-sensitive and -resistant colorectal cancer (CRC) cells. The purpose of the present study was to investigate the antitumor potential of LCB against human colorectal cancer in vitro and analyze its molecular mechanism of action. The viability of CRC cell lines was evaluated using the MTT assay. Flow cytometric analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In this study, we found that GLUD1 overexpression promotes HCC cells apoptosis through ROS induced MAPKs signaling pathway activation. In recent years, studies on the activation of p38/JNK MAPK signaling pathway and the induction of tumor cell apoptosis have been confirmed and explored in liver cancer, lung cancer, pancreatic cancer, colorectal cancer, and so on [38][39][40]. MAPKs signaling pathway are taken as promising targets for cancer therapy, and some compounds that act as activators of MAPKs signaling pathway exhibit inhibitory effects on cancer progression through inducing mitochondrial apoptosis of cancer cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that GLUD1 overexpression promotes HCC cells apoptosis through ROS induced MAPKs signaling pathway activation. In recent years, studies on the activation of p38/JNK MAPK signaling pathway and the induction of tumor cell apoptosis have been confirmed and explored in liver cancer, lung cancer, pancreatic cancer, colorectal cancer, and so on [38][39][40]. MAPKs signaling pathway are taken as promising targets for cancer therapy, and some compounds that act as activators of MAPKs signaling pathway exhibit inhibitory effects on cancer progression through inducing mitochondrial apoptosis of cancer cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the ERK/MAPK pathway plays a crucial role in regulating cell growth and differentiation, and its hyper-activation can trigger a cascade of intracellular responses, resulting in cell cycle arrest at the G1/S or G2/M checkpoints, thereby causing cell cycle blockage ( Kim & Choi, 2010 ). Additionally, the activation of JNK/MAPK and p38/MAPK signaling pathways may intensify the cellular response to oxidative stress, promoting the accumulation of ROS, which in turn affects the normal physiological functions of the cell ( Wang et al, 2018 ; Kwak et al, 2023 ). As a tumor suppressor protein, p53 plays a central role in how cells respond to DNA damage and stress ( Ou & Schumacher, 2018 ; Liebl & Hofmann, 2019 ; Vaddavalli & Schumacher, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Licochalcones regulate signaling pathways, including EGFR/ERK ( Gao et al ., 2021 ), PI3K/Akt/mTOR ( Xue et al ., 2018 ), p38/JNK ( Kwak et al ., 2023 ), JAK2/STAT3 ( Park et al ., 2022 ), MEK/ERK ( Park et al ., 2015 ), and MKK4/JNK ( Wu et al ., 2018 ), and their downstream protein expression. They have been shown to exert various biological effects on cancer cells, such as inducing autophagy and apoptosis and inhibiting cell proliferation, migration, and invasion ( Deng et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%